Perceived Effectiveness of Non-Monetray Rewards on South East Educational Region Employee Satisfaction. - Salani, End (Advances in Social Sciences Research Journal, 2017)
The study sought employee perceptions on the effects of non-monetary rewards on job satisfaction in South East Regional Education Office. To get some clues of perceptions, the South East Regional Education Office was selected through convenient sampling for the purpose of the study. From this region, employees of the headquarters of South East Regional Education office were involved. The study used a closed ended questionnaire and an interview schedule for data collection while the analysis of results was carried out using both qualitative and quantitative approaches. As an illustration, a one way ANOVA was used to test for differences in employees’ perceptions by gender, while data from interviews thematic analysis was used to analyse data. The findings revealed that majority of the employees felt they were not involved in decision making processes and that they were not recognised for efforts made in the execution of their duties. Furthermore, most of the employees felt that they were not empowered to acquire skills that would enable them to take independent decisions. Male employees indicated that there was minimal delegation of responsibilities. The employees also decried lack of teamwork among members of the organisation, a situation that is detrimental to the success of the organisation. It is recommended that supervisors should employ non-monetary rewards in the form of providing job enrichment activities supported by mentoring and coaching. Regular meetings across different cadres should be scheduled to promote employee involvement in decision making processes. Also it has to be further studied the types of support supervisors needed in order to effectively integrate non-monetary rewards in their supervision structures.